SUNTINGAN TEKS SULUK LINGLUNG SEH MALAYA KARYA SUNAN KALIJAGA - Muhammad Safii (Haluan Sastra Budaya, 2023)
Suluk Linglung Seh Malaya is a monumental work of a famous wali, Sunan Kalijaga beyond a great preaching by mind of the performing art, the sunan also preaches through the of written literature, one of which is the mangripta 'writing' the suluk. From this research, researcher found three editions of the manuscript: 1. Collection of R.Ay. Supratini Mursyidi-R. Iman Anom, 2. Uigerverij en Booekhaldel Surakarta- University of Indonesia, 3. Museum of Sanabudaya Yogyakarta; therefore, The Manuscript of Suluk Linglung Seh Malaya is classified as a Plural manuscript edition. The aim of this research is to present an edited text of Suluk Linglung Seh Malaya that is undefiled by error, so that the general public is able to read and understand a manuscript. Furthermore, content analysis is to analyze the contents of the manuscript. This research used Philology approach. The method used a mixed-method by mean of the standard editing method. Which is to correct. It used a standardized dictionary or ruler. From this research, it appears the efforts the Seh Malaya or Sunan Kalijaga, in seeking the perfection of life and drawing out knowledge from Sunan Bonang afterwards.